2022
DOI: 10.31083/j.fbl2707209
|View full text |Cite
|
Sign up to set email alerts
|

Trafficking and Gating Cooperation Between Deficient Nav1.5-mutant Channels to Rescue INa

Abstract: Background: Pathogenic variants in SCN5A, the gene encoding the cardiac Na + channel α-subunit Nav1.5, result in life-threatening arrhythmias, e.g., Brugada syndrome, cardiac conduction defects and long QT syndrome. This variety of phenotypes is underlied by the fact that each Nav1.5 mutation has unique consequences on the channel trafficking and gating capabilities. Recently, we established that sodium channel α-subunits Nav1.5, Nav1.1 and Nav1.2 could dimerize, thus, explaining the potency of some Nav1.5 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Another explanation for the observed AP initiation properties was associated with the expression of multiple voltage-gated channels or their gating mechanism. Cooperative gating between sodium channels was suggested to reproduce the sharp AP onset and variability in modeling studies [16,33], which was supported by recent evidence in cardiac Na_v1.5 [34][35][36][37]. On the other hand, changes in resting potential could influence neuronal excitability and hence the AP shape.…”
Section: Discussionmentioning
confidence: 55%
“…Another explanation for the observed AP initiation properties was associated with the expression of multiple voltage-gated channels or their gating mechanism. Cooperative gating between sodium channels was suggested to reproduce the sharp AP onset and variability in modeling studies [16,33], which was supported by recent evidence in cardiac Na_v1.5 [34][35][36][37]. On the other hand, changes in resting potential could influence neuronal excitability and hence the AP shape.…”
Section: Discussionmentioning
confidence: 55%
“…Variants in the Na + channel were discovered to be linked with a trafficking defect, leading to HF ( 212 ). A recent study demonstrated that two different variants of Nav1.5 can interact with each other to rescue the I Na ( 181 ). Specifically, this study showed that one variant of Na + channel, trafficking-deficient but gating-competent, was able to restore a fraction of the I Na by interacting with another Na + channel variant that was trafficking-competent but gating-deficient.…”
Section: Ion Channel Trafficking Defect Contributes To the Developmen...mentioning
confidence: 99%
“…12 For instance, some loss-offunction mutants exerting dominant-negative effect were shown to impact biosynthesis, degradation, cell surface addressment, and functional output of the wildtype Na v 1.5 presumably due to oligomerization between the channels. 13,14 Therefore, identification of the sites or domains of Na v 1.5 responsible for its oligomerization could provide new insights into the molecular mechanisms underlying cardiac arrhythmias. This review discusses the current literature describing several proposed mechanisms of Na v 1.5 oligomerization: 1) direct cis-interactions of α-subunits; 2) indirect cis-interactions mediated by 14-3-3 proteins; and 3) indirect cis-and trans-interactions mediated by auxiliary subunits.…”
Section: Introductionmentioning
confidence: 99%